Fontes e parcelamento do nitrogênio em cobertura, na cultura do milho sob plantio direto - De M. Cardoso, Susiane [UNESP]; Soratto, Rogério Peres [UNESP]; Da Silva, Ángela H.; De Mendonça, Cristiane G. (Revista Brasileira de Ciencias Agrarias, 2011)
The effect of the split-application of different sidedressed nitrogen sources on maize crop under zero tillage, in a sandy soil, was evaluated. A randomized block design was used in a factorial scheme of 3x3+1, with four replications. Treatments consisted of three nitrogen sources (urea, urea extruded with starch (Amiréia® 180S) and ammonium sulfonitrate with nitrification inhibitor of 3.4-dimethylpyrazole phosphate (Entec® 26)), three nitrogen split-application (120, 60+60 e 40+40+40 kg ha-1, applied as sidedressing, when the plants showed 4, 8, and 12 expanded leaves, respectively), and one control (without sidedressed N). Entec® applied in a unique dose when plants had 4 expanded leaves resulted in greater N concentration on the maize leaves. Sidedressing nitrogen application resulted in higher plant and ear heights, number of grains per ear and grain yield. Sidedressing nitrogen split-application did not influence the yield components and grain yield of the maize crop grown under zero tillage in sandy soil, regardless of the nitrogen source.
Sidedressing nitrogen sources and splitting on maize under no-tillage system
Keywords: Dimethylpyrazole phosphate; Nitrogen fertilization; Sulfonitrate; Urea; Zea mays; Embryophyta; Tracheophyta